Answer: see proof below
Explanation:
* Use the following Co-function Identity: sin A = cos(90 - A)
* Use the following Sum to Product Identities:
cos x - cos y = 2 sin [(x + y)/2] · sin [(x - y)/2]
cos x + cos y = 2 cos [(x + y)/2] · cos [(x - y)/2]
* Use the Unit Circle to evaluate cos 45 = sin 45 = √2/2
Proof LHS → RHS
![\text{LHS:}\qquad \qquad \qquad \qquad \quad (\cos 10-\sin 10)/(\cos 10+\sin 10)\\\\\\\text{Co-function Identity:}\qquad (\cos 10 -\cos (90-10))/(\cos 10+\cos (90-10))\\\\\\\text{Product to Sum Identity:}\quad (2\sin ((10+80)/(2))\sin ((80-10)/(2)))/(2\cos ((10+80)/(2))\cos ((80-10)/(2)))\\\\\\\text{Simplify:}\qquad \qquad \qquad \qquad (2\sin (45)\sin (35))/(2 \cos (45)\cos (35))](https://img.qammunity.org/2021/formulas/mathematics/high-school/55p72fi4qaymna6xpwk77bfa7xxlc5e1lj.png)
![.\qquad \qquad \qquad \qquad \qquad = (2((\sqrt2)/(2)) \sin (35))/(2((\sqrt2)/(2)) \cos(35))\\\\\\.\qquad \qquad \qquad \qquad \qquad = \tan (35)](https://img.qammunity.org/2021/formulas/mathematics/high-school/5p6q46p3ohv7tl5giklcwh490dpklyp51m.png)
LHS = RHS: tan 35 = tan 35